Recurrent Multivalvular Staphylococcus Lugdunensis Endocarditis Causing Complete Heart Block after TAVR - Preeti Singhal; Somsupha Kanjanauthai; Wilson Kwan (Case Reports in Cardiology)
Prosthetic valve endocarditis after transcatheter aortic valve replacement (PVE after TAVR) is a feared complication most often observed during the early postprocedural period. We report a case of severe, multivalvular PVE after TAVR with complete heart block caused by an uncommon organism. A 78-year-old female with prior Streptococcus agalactiae mitral valve endocarditis treated with antibiotics presented one year later with severe, symptomatic aortic insufficiency. She subsequently underwent TAVR given high surgical risk. Six weeks post-TAVR, she presented with syncope, fever, and complete heart block. Transthoracic echocardiogram was not demonstrative of vegetation. Blood cultures were positive for Staphylococcus lugdunensis. Transesophageal echocardiogram (TEE) demonstrated vegetations of the aortic, mitral, and tricuspid valves and aorto-mitral continuity. While awaiting surgery, the patient developed cardiac arrest; she was resuscitated and taken to surgery emergently. The patient underwent TAVR explantation, bovine pericardial tissue aortic and porcine bioprosthetic mitral valve replacements, and tricuspid valve repair. Additionally, left main coronary artery endarterectomy was performed due to presence of infectious vegetative material. Staphylococcus lugdunensis is an unusual but virulent organism that may damage both native and prosthetic valves. Early surgery is recommended for PVE after TAVR, especially in cases with perivalvular disease causing conduction abnormalities. Learning Objectives. TAVR has revolutionized the management of severe aortic stenosis and has even been successfully utilized in select cases of aortic regurgitation. Unfortunately, there are a number of associated complications that can be difficult to diagnose, such as prosthetic valve endocarditis (PVE). We emphasize maintaining a high clinical suspicion for PVE after TAVR in patients presenting with conduction abnormalities and highlight the importance of early surgical management in cases complicated by heart block, abscesses, or destructive penetrating lesions.